A randomized Phase III trial of neoadjuvant recombinant human endostatin, docetaxel and epirubicin as first‐line therapy for patients with breast cancer (CBCRT01). Issue 10 (23rd December 2017) - Chen, Jianghao; Yao, Qing; Huang, Meiling; Wang, Bo; Zhang, Juliang; Wang, Ting; Ming, Yu; Zhou, Xiaodong; Jia, Qianxin; Huan, Yi; Wang, Jing; Wang, Ling
Abstract : To further assess the efficacy and safety of recombinant human endostatin (rh‐endostatin), a Phase III, multicenter, prospective, randomized, controlled clinical trial was conducted. Patients to be treated with neoadjuvant docetaxel and epirubicin (DE) or DE plus rh‐endostatin (DEE) were eligible for this trial. The primary endpoint was clinical/pathological response. Secondary endpoints included adverse events and quality of life (QOL). Finally, 803 patients were enrolled and randomly assigned to receive DE ( n = 402) or DEE ( n = 401) regimen. After three cycles of neoadjuvant therapy, "complete response" achieved in 14.2% of patients in DEE group versus 6.7% in DE group, "partial response" achieved in 76.8% versus 71.1%, while "stable disease" in 6.0% versus 18.9%, "progressive disease" in 3.0% versus 3.2% of patients. The rate of objective response in DEE and DE group was 91.0% and 77.9%, respectively ( p < 0.001). In spite of a relatively higher pathological complete response achieved following the combination therapy, no significant difference was found between two arms. Adverse events were mostly of Grades 1–2. No significant difference in adverse event and QOL was found between the two arms. In conclusion, the combination of chemotherapy and rh‐endostatin achieved better outcomes than chemotherapy alone, and thus can be considered as a promising therapeutic strategy for breast cancer. Abstract : What's new? Because solid tumors rely on new blood vessels to grow larger and to metastasize, a number of antiangiogenic drugs are now used in the clinic or are in development. In this Phase III clinical study in breast‐cancer patients, the authors tested a new drug candidate called "recombinant human endostatin" (rh‐endostatin), in combination with neoadjuvant chemotherapy. They found that the combination yielded significantly better outcomes than the chemotherapy alone. These results support rh‐endostatin as part of a promising therapeutic strategy for breast cancer.